2021
DOI: 10.4103/jcrt.jcrt_410_19
|View full text |Cite
|
Sign up to set email alerts
|

The esophageal dose–volume parameters for predicting Grade I–II acute esophagitis correlated with weight loss and serum albumin decrease in lung cancer radiotherapy

Abstract: Introduction: Acute esophagitis (AE) is a commonly encountered side effect of curative thoracic radiotherapy (CTRT) for lung cancer patients. Nevertheless, its identification for widely used scoring systems depends on patients' statements. It is aimed to evaluate the correlation between the esophagus doses during CTRT and Grade 1–2 AE, weight change, and change in serum albumin (Alb) levels. Subjects and Methods: The data collected from 124 lung cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Opioids alleviate pain and reduce inflammation, improving immunotherapy efficacy. Lastly, the body’s ALB level reflects the patient’s nutritional status and indicates the patient’s liver function reserve and treatment tolerance [ 39 , 40 ]. Therefore, considering systemic inflammation and ALB levels aids understanding of the immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Opioids alleviate pain and reduce inflammation, improving immunotherapy efficacy. Lastly, the body’s ALB level reflects the patient’s nutritional status and indicates the patient’s liver function reserve and treatment tolerance [ 39 , 40 ]. Therefore, considering systemic inflammation and ALB levels aids understanding of the immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation can deplete the nutrient reserves in the body, and lead to persistent activation of immune cells and inflammatory responses, thereby inhibiting the immune response to tumors and enhancing tumor escape mechanisms (61,62). Albumin levels and weight not only reflect the nutritional status of patients, but also indicate their liver function reserve and treatment tolerance (63,64). Furthermore, 'a previous study reported that low levels of serum albumin are associated with systemic inflammation (65).…”
Section: Discussionmentioning
confidence: 99%
“…[ 12 ] found that Alb < 35 g/L generally represented a poor prognosis for patients with metastatic non-small cell lung cancer (mNSCLC). The level of Alb can also predict the occurrence of adverse reactions in lung cancer patients after treatment [ 13 ]. A clinical study by Kazuki et al.…”
Section: Introductionmentioning
confidence: 99%